2021
DOI: 10.1590/1678-992x-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Immunocastration on performance and meat quality of Bos indicus (Nellore) cattle under different nutritional systems

Abstract: The present study aimed to evaluate the effects of immunocastration on the animal growth, carcass traits, and meat quality of Nellore cattle receiving or not Ionophore supplementation at pasture or pasture with concentrate (semi-feedlot). The first experiment (Pasture) was carried out during the rainy season, while the second (supplemented = Semifeedlot) was conducted during the dry season. In each assessment, 60 males were allocated into three treatments, in a completely randomized design: non-castrated, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(42 reference statements)
0
1
1
2
Order By: Relevance
“…After slaughter, muscle glycogen is used as an energy source, leading to accumulation of lactic acid and hydrogen ions, resulting in a reduction in pH (GOMES, 2021). Non-castrated animals are more susceptible to a reduction in muscle glycogen, leading to lower lactic acid production, which results in a higher pH (JACINTO-VALDERRAMA et al, 2021), but this characteristic was not detected in this study.…”
Section: Carcass Finish Degreecontrasting
confidence: 71%
“…After slaughter, muscle glycogen is used as an energy source, leading to accumulation of lactic acid and hydrogen ions, resulting in a reduction in pH (GOMES, 2021). Non-castrated animals are more susceptible to a reduction in muscle glycogen, leading to lower lactic acid production, which results in a higher pH (JACINTO-VALDERRAMA et al, 2021), but this characteristic was not detected in this study.…”
Section: Carcass Finish Degreecontrasting
confidence: 71%
“…At 12 months of age, differences between bulls and steers in cartilage development were negligible; however, at older ages, bull carcasses consistently exhibited a more advanced maturity [ 41 ]. Jacinto-Valderrama et al [ 55 ], working with Nellore cattle, also reported that the bone physiological maturity of carcasses revealed that bulls, regardless of the production system (grazing vs. semi-confinement), were significantly older than immuno-castrated steers.…”
Section: Resultsmentioning
confidence: 99%
“…En este sentido, se ha reportado una mayor presencia de DFD en machos, comparado con hembras (46); lo cual se explica por la relación entre la testosterona y el comportamiento agresivo, mayor actividad física y estrés fisiológico en los animales. Por esta razón, la inmunocastración ha sido asociada con una mejor calidad de la canal (47). Por otra parte, el estado fisiológico y su influencia hormonal en las hembras, también ha sido referenciado como un factor que afecta significativamente la presencia de la condición DFD, toda vez que Kawecki et al (45) reportaron mayor frecuencia de carne DFD en vacas que en novillas.…”
Section: Factores Pre Y Post Beneficio Que Afectan La Presencia De Ca...unclassified